Multiradionuclide evidence for an extreme solar proton event around 2,610 B.P. (∼660 BC) - O’Hare, Paschal; Mekhaldi, Florian; Adolphi, Florian; Raisbeck, Grant; Aldahan, Ala; Anderberg, Emma; Beer, Jürg; Christl, Marcus; Fahrni, Simon; Synal, Hans-Arno; Park, Junghun; Possnert, Göran; et al. (Proceedings of the National Academy of Sciences, 2019)
International audience Recently, it has been confirmed that extreme solar proton events can lead to significantly increased atmospheric production rates of cosmogenic radionuclides. Evidence of such events is recorded in annually resolved natural archives, such as tree rings [carbon-14 (C-14)] and ice cores [beryllium-10 (Be-10), chlorine-36 (Cl-36)]. Here, we show evidence for an extreme solar event around 2,610 years B.P. (similar to 660 BC) based on high-resolution Be-10 data from two Greenland ice cores. Our conclusions are supported by modeled C-14 production rates for the same period. Using existing Cl-36 ice core data in conjunction with Be-10, we further show that this solar event was characterized by a very hard energy spectrum. These results indicate that the 2,610-years B.P. event was an order of magnitude stronger than any solar event recorded during the instrumental period and comparable with the solar proton event of AD 774/775, the largest solar event known to date. The results illustrate the importance of multiple ice core radionuclide measurements for the reliable identification of short-term production rate increases and the assessment of their origins.